Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00012-005-1958-5
|View full text |Cite
|
Sign up to set email alerts
|

Locally finite varieties of Heyting algebras

Abstract: We show that for a variety V of Heyting algebras the following conditions are equivalent: (1) V is locally finite; (2) the V-coproduct of any two finite V-algebras is finite;(3) either V coincides with the variety of Boolean algebras or finite V-copowers of the three element chain 3 ∈ V are finite. We also show that a variety V of Heyting algebras is generated by its finite members if, and only if, V is generated by a locally finite V-algebra. Finally, to the two existing criteria for varieties of Heyting alge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…Consider, as an example, the variety of Heyting algebras. Drawing on results of L. Maximova [51] and Bezhanishvili and Grigolia [5,Theorem 4.1], we obtain that a variety V of Heyting algebras satisfies (the equivalent) conditions (1)-(4) of Theorem 5.1 if and only if V contains none of (a) the variety generated by all finite Heyting chains, that is, the variety L of relative Stone algebras; (b) the variety generated by algebras B ⊕ 1, where B is a Boolean algebra; (c) the variety generated by algebras 1⊕B⊕1, where B is a Boolean algebra.…”
Section: Varieties Of Lattices and Lattice-based Algebrasmentioning
confidence: 99%
“…Consider, as an example, the variety of Heyting algebras. Drawing on results of L. Maximova [51] and Bezhanishvili and Grigolia [5,Theorem 4.1], we obtain that a variety V of Heyting algebras satisfies (the equivalent) conditions (1)-(4) of Theorem 5.1 if and only if V contains none of (a) the variety generated by all finite Heyting chains, that is, the variety L of relative Stone algebras; (b) the variety generated by algebras B ⊕ 1, where B is a Boolean algebra; (c) the variety generated by algebras 1⊕B⊕1, where B is a Boolean algebra.…”
Section: Varieties Of Lattices and Lattice-based Algebrasmentioning
confidence: 99%
“…V has only finitely many subvarieties. 4. The dual space of every algebra in V has finite depth and finite width.…”
Section: Finitely Generated Varieties Of Heyting Algebrasmentioning
confidence: 99%
“…Alternative characterizations were given in [4][5][6]. Let V 1 denote the variety of Heyting algebras generated by finite chains, let V 2 denote the variety of Heyting algebras generated by finite Boolean algebras with a new adjoined top, and let V 3 denote the variety of Heyting algebras generated by finite Boolean algebras with a new adjoined top and bottom.…”
Section: Finitely Generated Varieties Of Heyting Algebrasmentioning
confidence: 99%
“…Mardaev [19] showed that, unlike extensions of S4, there are continuum pre-locally tabular intermediate logics. G. Bezhanishvili and Grigolia [3] gave a characterization of locally tabular intermediate logics using coproducts of three element Heyting algebra. They also conjectured that an intermediate logic L is locally tabular iff the 2-generated free algebra in the corresponding variety is finite.…”
Section: Locally Tabular and Tabular Intermediate Logicsmentioning
confidence: 99%